Getting "Beyond the Fence" (ATI reference 27) - Shook, Jarod; Piché, Justin; Walby, Kevin (Université d'Ottawa | University of Ottawa, 2018)
In 2015, Correctional Service Canada launched a virtual tour promising a 'first-hand' and 'realistic' depiction of life and work inside a federal penitentiary titled Beyond the Fence. Based on an analysis of Access to Information disclosures, we examine the backstage activities that went into the production, marketing, and evaluation of the tour. Drawing on Goffman's (1959) notions of frontstage and backstage, as well as MacCannell's (1973) idea of staged authenticity, we reveal how representations of incarceration and punishment were sanitized to build legitimacy and consent for carceralism. We conclude by reflecting on the need to study the content and form of state representations of penality, and the challenges that representations pose to working toward a future without carceral institutions.
Keywords: imprisonment; carceral expansion; carceral tours; representations; Access to Information